Differential Hydration of Ice‐Binding Surface of Globular and Hyperactive Antifreeze Proteins. Issue 8 (8th July 2021) - Pal, Prasun; Chakraborty, Sandipan; Jana, Biman
Abstract: Like hyperactive antifreeze proteins (AFPs), globular AFPs also illustrate thermal hysteresis by specific binding to ice. The ice‐binding surface (IBS) topology and residue preferences are different between globular AFPs and hyperactive AFPs. This study explores the hydration water ordering and its temperature and length‐scale dependencies for type‐III AFPs, and the results with hyperactive AFP and non‐AFPs are compared. The hydration layer of the IBS of globular AFP is semiclathrate‐like, which is different from the hyperactive AFPs, as it is reported to be ice‐like. In a similar environment, the solvation water surrounding the non‐ice‐binding surface (non‐IBS) is mostly liquid‐like. Surprisingly, the non‐IBS is appreciably dissimilar from the non‐AFP in terms of hydration pattern. The amino acid compositions of the non‐IBS are in contrast with the IBS. Protein–water hydrogen bonding patterns between the IBS and non‐IBS of AFP are also different. These consequences suggest the collective function of non‐IBS and IBS in the antifreeze activity. The different nature of the first solvation shell water ordering around the IBS of type‐III AFP and hyperactive insect AFP implicates a differential design of IBS that may account for their observed difference in antifreeze activity. Abstract : The water around ice‐binding surface (IBS) of hyperactive antifreeze proteins (AFPs) shows ice‐like ordering, while IBS of type‐III AFPs prefers semiclathrate‐like order of its hydration water. Such a difference in the hydration layer structure is possibly responsible for the observed differences in the binding plane specificity for these two different types of AFPs.